Vapor phase synthesis of ferroelectric microislands on PVDF thin films - Mohammadmoradi, Omid; Celik, Umit; Misirlioglu, I. Burc; Ince, Gozde Ozaydin (Iop Publishing Ltd, 2021)
The interest in patterned polyvinylidene fluoride (PVDF) surfaces has grown significantly in the recent years due to ability to control the ferroelectric behavior through the size and shape of the surface structures. However, forming micron sized structures on the PVDF surface generally requires laborious lithography based methods or use of templates which complicates the process. In this study, we report spontaneous formation of microislands with ferroelectric response during PVDF growth via initiated chemical vapor deposition. Depositions performed under continuous and no flow conditions show that laminar precursor flow to the surface yield homogenous thin films, whereas no flow conditions of the batch mode result in the growth of surface protrusions (microislands) with higher polar phase content. Formation of these surface instabilities after an incubation time indicates the presence of local stress fields building with time, resulting in formation of the islands with higher beta phase fraction to release the stress. Furthermore, the increased mobility of the polymer chains at high temperatures reduces the stress field, leading to lower beta/alpha phase ratios in smaller microislands.
Keywords: polyvinyl difluoride (PVDF) thin film; closed-batch initiated chemical vapor deposition (CB-iCVD); electrostatic force microscopy (EFM); ferroelectricity